Leveraging the blue economy to transform marine forest restoration. Issue 2 (23rd March 2022) - Filbee‐Dexter, Karen; Wernberg, Thomas; Barreiro, Rodolfo; Coleman, Melinda A.; de Bettignies, Thibaut; Feehan, Colette J.; Franco, Joao N.; Hasler, Berit; Louro, Ines; Norderhaug, Kjell M.; Staehr, Peter A. U.; Tuya, Fernando; et al.
Abstract : The UN Decade of Ecosystem Restoration is a response to the urgent need to substantially accelerate and upscale ecological restoration to secure Earth's sustainable future. Globally, restoration commitments have focused overwhelmingly on terrestrial forests. In contrast, despite a strong value proposition, efforts to restore seaweed forests lag far behind other major ecosystems and continue to be dominated by small‐scale, short‐term academic experiments. However, seaweed forest restoration can match the scale of damage and threat if moved from academia into the hands of community groups, industry, and restoration practitioners. Connecting two rapidly growing sectors in the Blue Economy—seaweed cultivation and the restoration industry—can transform marine forest restoration into a commercial‐scale enterprise that can make a significant contribution to global restoration efforts.